The understanding and analysis of reality: approaches to Marx’s method - Redon, Silvio; Campos, Eliane Christine Santos de (Argumentum, 2021)
Marx's method is an evident way of approaching and understanding reality and is able to consider its internal contradictions and the relationships between its constituent elements. This text, utilizing a literature review relevant to the theme, is intended to contribute to its understanding, given its complexity and scarce primary sources. To do so, we prioritize the main Marxian concepts and categories, provide opportunities to get close to the Marx’s analysis and add a brief theoretical contextualization of its development.